PENGUATAN IMAN ANAK CALON PENERIMA KOMUNI PERTAMA MELALUIKEGIATAN PEMBINAAN TENTANG MAKNA EKARISTI - Yohanes Juan Kromen; Agnes Oktavia Siba; Maria Asumta Boi Tokan (CV. Adiba Aisha Amira, 2026)
This study aims to analyze efforts to strengthen the faith of children who are candidates for First Communion through activities about the meaning of Eucharist. The background of this study is based on the limited understanding of the Eucharist as the source, center, and peak of Christian faith life. The method used is a qualitative approach with a descriptive research type. The subjects of the study consisted of children who are candidates for First Communion who participated in coaching activities at school. Data collection techniques were carried out through observasion, interviews, and documentation. The results of the study indicate that activities are dedicated and use participatory methods are able to increase children’s understanding of meaning of the Eucharist, wich in turn has an impact on strengthening children’s faith. Children show changes in attitudes, such as increased awareness, to participate in the Eucharist celebration and active involvement in Church activities. Thus, coaching about the meaning of the Eucharist plays an important role in preparing children’s faith to receive First Communion. This study recommends that coaching activities about the meaning of the Eucharist be carried out continuously with methods that are appropriate to children’s development.